Ethical Decision Making: Introduction to Cases and Concepts in Ethics - Newton, Lisa. author. aut Link
V, 63 p.
Keywords: This short introduction to the discipline of Ethics in its practical and professional applications teaches, in simplest form, the discipline's vocabulary and forms of reasoning. It includes illustrative cases, clear explanations of philosophical terminology, and presents decision procedures appropriate to a hierarchy of cases. It is meant to be a foundation for elementary work in Ethics.